ETNOMATHEMATICS EXPLORATION IN THE CULTURE SYSTEM OF MALAY CULTURE IN NAGA MAHAP VILLAGE - Medlyn Claudyasuka Patari; Dewi Risalah; Sandie Sandie; Saiful Bahri; Emi Tipuk Lestari (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2022)
Ethnomathematics is the study of mathematics' distinctive characteristics or colors as they exist and develop in society. Ethnomathematics is the study of mathematics as it appears or is utilized in cultural community groups such as urban and rural communities, children of a specific age, labor groups and indigenous peoples. For the vast majority of Indonesians, cultivation is a way of life, particularly the residents of Nanga Mahap Village. Mathematical words are employed in farming activities, ranging from units to fundamental mathematical concepts. Cultivation systems have been practiced in grasslands and forests around the world. Cultivation is a shifting cultivation system from one plot of land to another, usually cleared by cutting down and burning part of the forest to make fields. The goal of this study was to investigate the mathematical principles inherent in the Malay culture's farming system in Nanga Mahap Village. This is a qualitative study with an a ethnographic approach. This is a qualitative research that makes use of an ethnographic approach.. The study took place in Nanga Mahap Village, Sekadau Regency's Nanga Mahap District. The subjects of this research are informants, namely field farmers with Malay culture in Nanga Mahap Village. Data were gathered from a variety of sources including observation, interviewing, and documentation procedures. The results indicated that the farming system incorporated a mathematical element through the requirement for seeds, yields, and tools, namely the concept of comparison, the concept of counting mathematical words, tessellation (tiling), geometry, and congruence